Energy‐efficient power allocation in underlay and overlay cognitive device‐to‐device communications. Issue 2 (1st January 2019) - Sultana, Ajmery; Zhao, Lian; Fernando, Xavier
Abstract : Device‐to‐device (D2D) communication can effectively use cognitive radio network approach to coexist with cellular users. For such a cognitive D2D system, two approaches (underlay and overlay) are considered to manage the spectrum sharing among the cellular (primary) users and the D2D (secondary) users. Energy efficiency (EE) is crucial in both these cases due to limited battery capacity and quality of service requirements of the D2D users. This study effectively models the power allocation problem of such a cognitive D2D system by maximising the EE of the D2D users subject to a minimum rate requirement for both the D2D users and the cellular users. This leads to a non‐linear fractional optimisation problem which is more complicated and computationally intractable. Alternatively, geometric water‐filling approach have been utilised for power allocation to solve this optimisation problem which results in an ' exact ' and ' low complexity ' solution. Simulation results reveal the benefits of the proposed algorithm.